(untitled) (Editora Impacto Científico, 2024)
This study aimed to analyze the applicability of the AQPC (Qualitative Evaluation of Menu Preparations) as a quality management tool in Food and Nutrition Units (UAN). The methodology relied on a bibliographic review emphasizing SciELO articles, including quality indices (IQR) and real consumption studies (self-service). Findings from Gorgulho et al. (2011) and Savio et al. (2005) indicate a persistent inadequacy in meal offerings, marked by excess fat and high nutritional risk among users. The AQPC and the Preparation Technical Card (FTP) emerge as interconnected pillars to address this issue. AQPC functions as a feedback mechanism, verifying technical and sensory quality, while FTP ensures process standardization and rationalization. It is concluded that the integrated application of AQPC and FTP transforms the UAN into a managerial intervention agent, crucial for mitigating risks and promoting the health of the served population. DOI: https://doi.org/10.56238/edimpacto2025.090-032